Effects of Genital Nerve Stimulation Amplitude on Bladder Capacity in Spinal Cord Injured Subjects. (24th June 2019) - Yeh, Shauh-Der; Lin, Bor-Shing; Chen, Shih-Ching; Chen, Chih-Hwa; Gustafson, Kenneth J.; Bourbeau, Dennis J.; Rajneesh, Chellappan Praveen; Peng, Chih-Wei
Abstract : Background/Purpose . Few studies have investigated the effects of changing the amplitude of dorsal genital nerve stimulation (GNS) on the inhibition of neurogenic detrusor overactivity in individuals with spinal cord injury (SCI). The present study determined the acute effects of changes in GNS amplitude on bladder capacity gain in individuals with SCI and neurogenic detrusor overactivity. Methods . Cystometry was used to assess the effects of continuous GNS on bladder capacity during bladder filling. The cystometric trials were conducted in a randomized sequence of cystometric fills with continuous GNS at stimulation amplitudes ranging from 1 to 4 times of threshold (T) required to elicit the genitoanal reflex. Results . The bladder capacity increased minimally and maximally by approximately 34% and 77%, respectively, of the baseline bladder capacity at 1.5 T and 3.2 T, respectively. Stimulation amplitude and bladder capacity were significantly correlated ( R = 0.55, P = 0.01). Conclusion . This study demonstrates a linear correlation between the stimulation amplitude ranging from 1 to 4T and bladder capacity gain in individuals with SCI in acute GNS experiments. However, GNS amplitude out of the range of 1-4T might not be exactly a linear relationship due to subthreshold or saturation factors. Thus, further research is needed to examine this issue. Nevertheless, these results may be critical in laying the groundwork for understanding the effectiveness of acute GNS in the treatment of neurogenic detrusor overactivity.